Citations in Hypermedia: Implementation Issues - Jörgensen, Peter (Information Technology and Libraries, 2005)
Internet sources are increasingly used in scholarly work at all levels, yet it is often difficult to collect the information needed to cite these sources properly. The author proposes a method by which bibliographic information embedded in electronic sources could be automatically extracted when needed and discusses existing standards that could be utilized to accomplish this and impediments to implementation.